GRAPHIC FORMALIZATION IN SOLVING VISUAL DESIGN TASKS - Berdynskykh, Sviatoslav; Solopov Vіacheslav; Latiy, Oksana; Yakiviuk, Olena (Theory and practice of design, 2025)
Purpose. The aim of this article is to investigate the application of graphic formalization in design practice and to analyze specific methods of executing formalized visualizations using contemporary tools. Methodology. The study employs theoretical methods of analysis and synthesis, analogy-based formalization, observation, comparison, and comparative-typological analysis. It draws on theoretical principles and recommendations developed by American artist W. Bowman for the effective visual representation of scientific and technical information. The research materials include designer portfolios and samples of printed products that utilize efficient visualizations to convey information. Results. The growing integration of new digital graphic tools significantly expands operational capacities in image construction. The pursuit of concise and comprehensive forms of information transmission is inherently tied to communication objectives, as affirmed by design theorists. Throughout the evolution of graphic tools, a range of techniques has been developed for the effective depiction of object properties – both visible and hidden – which facilitate the construction of visual models for analyzing and conceptualizing various aspects of design tasks. The present study focuses on key aspects such as appearance, structure, organization, functionality, quantitative relationships, and spatial positioning. The influence of formalized imagery on the creative process is also explored. It is demonstrated that the graphic formalization of these characteristics not only enhances the informativeness of the design outcome but also directs the designer toward more effective and qualitative exploration, broadens conceptual perspectives, and stimulates task reinterpretation and idea generation. Other issues related to formalization involve the development of symbols, pictograms, icons, and information graphics that convey substantial information through simple and comprehensible forms. The article outlines key principles of image formalization in the creation of such graphic products. Scientific novelty. This research reveals an underexplored property of formalization in design tasks and significantly broadens the understanding of its techniques within design practice. Practical relevance. The findings can be applied in professional design practice, educational processes, and further research in art history, architecture, and design.